EPISTEMOLOGICAL BASIS OF ACCOUNTING: A PHILOSOPHICAL CRITICISM - Wahdi, Nirsetyo; Gusmao, Cristino; S. Amaral, Adolmando; Luhgiatno, Luhgiatno; Santoso, Aprih (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2025)
Current accounting tends to be more materialistic, selfish, and secular because it strongly emphasizes material and value-free accounting. Numerous examples of anomalies and manipulation of financial statements carried out by accountants that demonstrate these characteristics are evidence. This problem is exacerbated by the assumption that humans are homo economicus who are opportunistic, greedy, and selfish. This raises a key question about the character of accountants and accounting science. Accounting science is very different from philosophy. Achieving the ultimate truth of science and the true nature of science is the foundation of accounting science. This study aims to examine the philosophy and evolution of accounting as well as practical strategies to reduce financial statement variance. According to the findings of this research, accounting theorists can consider and adopt various paradigms from other disciplines to address the complex problems that accounting is currently facing and will face. These paradigms are based on philosophical differences in science.